1981
DOI: 10.2307/3033704
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Identity and Role Performance

Abstract: Despite interest in the influence of self-concept on behavior, research has been limited by (I) the need to better understand the mechanism by which self influences role behaviors, (2) a reliance on self-esteem as the only measure of self-concept, and (3) the absence of quantitative measures of self-concept. The research reported here is designed to test one formulation ofthe link between identity and behavior. It is based on recent theoretical conceptions of identity, advances in its measurement, and the assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
370
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(400 citation statements)
references
References 17 publications
9
370
1
10
Order By: Relevance
“…Students were self-selecting and the study did not discriminate on grounds of gender. The research methodology used was based upon previous work into identity analysis and online working (Burke, et al, 1981), in which a feminist, postmodern phenomenological approach into identity analysis was taken (Langridge, 2007). The phenomenological approach has been used across the public sector to investigate the ways in which professional identities change and evolve according to the circumstances in which they are operating (Baldwin, 2008;Baxter, 2011b;Burke, et al, 1981) and has been found to be particularly useful in uncovering underlying beliefs which, in turn, underlie actions and behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Students were self-selecting and the study did not discriminate on grounds of gender. The research methodology used was based upon previous work into identity analysis and online working (Burke, et al, 1981), in which a feminist, postmodern phenomenological approach into identity analysis was taken (Langridge, 2007). The phenomenological approach has been used across the public sector to investigate the ways in which professional identities change and evolve according to the circumstances in which they are operating (Baldwin, 2008;Baxter, 2011b;Burke, et al, 1981) and has been found to be particularly useful in uncovering underlying beliefs which, in turn, underlie actions and behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…The research methodology used was based upon previous work into identity analysis and online working (Burke, et al, 1981), in which a feminist, postmodern phenomenological approach into identity analysis was taken (Langridge, 2007). The phenomenological approach has been used across the public sector to investigate the ways in which professional identities change and evolve according to the circumstances in which they are operating (Baldwin, 2008;Baxter, 2011b;Burke, et al, 1981) and has been found to be particularly useful in uncovering underlying beliefs which, in turn, underlie actions and behaviors. It is also employed by feminist researchers, placing the individual at the heart of their story; their identity is that reflected in their articulation of their own story (Josselson, 1987(Josselson, , 2007Maclure, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' role identity development relies on the ways in which a teacher envisions him-or herself fulfilling the role of teacher through practice. These hypothetical visions of what type of teacher an individual hopes to become are referred to as role standards or designated identities (Burke & Reitzes, 1981;Collier, 2001;Sfard & Prusak, 2005). However, certain individuals have a disproportionately significant influence on role identity development.…”
Section: Identity and Role Identitymentioning
confidence: 99%
“…According to the assumptions that social identities have different salience that influence 'how much effort we put into each role and how well we perform it' (Burke & Reitzes, 1981) we attempted to explore the youth's national identity first of all through the prism of civic, territorial and retrospective identifications.…”
Section: National Identity Of Youth In the Light Of Civic And Territomentioning
confidence: 99%